Conversaciones con Shakespeare y Marlowe, la huella permanente del Nuevo Historicismo - Lorenzo, Eusebio de (Estudios Ingleses de la Universidad Complutense, 2006)
This article reviews the contents of two recent biographical studies of William Shakespeare and Christopher Marlowe written from a New Historicist perspective. The article discusses New Historicism and its principles as they are applied in these studies. The authors, Stephen Greenblatt and David Riggs, offer invaluable insights into the literary text as the repository of the social energies which circulated in the ideological domain of Elizabethan England. Such energies, operating upon the creative imagination of both Shakespeare and Marlowe, are visible not only in their plays or poems, but also in the institutions (the theater, the City, the church, the school or the university) where the authors lived. Therefore, both books present imaginative and profound accounts of Elizabethan society, underscoring the exposure of the artistic mind to that world. These publications demonstrate the more than active role that New Historicists have had in the US academic world for the past two decades. Even though these studies undoubtedly follow a scholarly, critical perspective based on extensive textual research, their format and style turn them into informative treatises addressed to an audience broader than the scholarly world.